2015
DOI: 10.3233/jad-141755
|View full text |Cite
|
Sign up to set email alerts
|

Increased Selenoprotein P in Choroid Plexus and Cerebrospinal Fluid in Alzheimer's Disease Brain

Abstract: Subjects with Alzheimer’s disease (AD) have elevated brain levels of the selenium transporter selenoprotein P (Sepp1). We investigated if this elevation results from increased release of Sepp1 from the choroid plexus (CP). Sepp1 is significantly increased in CP from AD brains in comparison to non-AD brains. Sepp1 localizes to the trans-Golgi network within CP epithelia, where it is processed for secretion. The cerebrospinal fluid from AD subjects also contains increased levels Sepp1 in comparison to non-AD sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…Moreover, patterns of Se species observed in serum of study subjects may not necessarily correspond to their distribution in other body districts and tissues, neither to what might be observed with very different types and amounts of Se exposure. In fact, laboratory and human studies have shown that relative distribution of Se species may differ according to the amount and type of dietary Se, as well as the body tissue and district under investigation and the disease status [51,57,[86][87][88][89][90][91], and even the correlation of the various Se species found in different compartments may vary greatly [20,51], thus highlighting the complexity of issues such as tissue-specific deposition and metabolism of the various Se species. Finally, it must be noted that, following ingestion of different Se species, retention of organic forms in body tissues is consistently higher than that of inorganic compounds [92], and therefore levels of Se species in serum (or other tissues) may not necessarily reflect the relative intake of these species through diet and other sources, nor their toxicity and biological effects [4,93].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patterns of Se species observed in serum of study subjects may not necessarily correspond to their distribution in other body districts and tissues, neither to what might be observed with very different types and amounts of Se exposure. In fact, laboratory and human studies have shown that relative distribution of Se species may differ according to the amount and type of dietary Se, as well as the body tissue and district under investigation and the disease status [51,57,[86][87][88][89][90][91], and even the correlation of the various Se species found in different compartments may vary greatly [20,51], thus highlighting the complexity of issues such as tissue-specific deposition and metabolism of the various Se species. Finally, it must be noted that, following ingestion of different Se species, retention of organic forms in body tissues is consistently higher than that of inorganic compounds [92], and therefore levels of Se species in serum (or other tissues) may not necessarily reflect the relative intake of these species through diet and other sources, nor their toxicity and biological effects [4,93].…”
Section: Discussionmentioning
confidence: 99%
“…We also consider it unlikely that such strongly increased selenium species levels were due to a compensatory response to a condition of oxidative stress, a mechanism which is well known to occur following environmental stressors including selenium itself [26] and which has been suggested to explain the excess selenoprotein P content in Alzheimer's disease brains [49]. In fact, in such a case we would have expected an increase limited to anti-oxidant selenium compounds, such as Se-GPx, Se-PP, and Se-TrxR, and not the other forms (such as Se-HSA and the inorganic ones, i.e., Se-IV and Se-VI) not belonging to the usual metabolic pathways for antioxidant selenoproteins synthesis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Summary information of subjects was published previously [19]. 10 μm sections of medial temporal cortex were deparaffinized, and ‘antigen unmasking’ was achieved by heating to 95°C at 15 psi in a pressure cooker in an alkaline/EDTA solution (Trilogy, Cell Marque), followed by 3 min in 90% formic acid.…”
Section: Methodsmentioning
confidence: 99%